2021
DOI: 10.32598/ppj.25.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin reduced cisplatin-induced hyperalgesia bysuppressing oxidative stress in male rats

Abstract: Introduction: Cisplatin is an antineoplastic agent which is used in treatment of various cancers. However its clinical use is associated with oxidative stress-mediated neuropathic pain. This research aimed to explore the effect of silymarin on cisplatin-induced hyperalgesia (CIH) and oxidative stress biomarkers in male rats. Methods: Fifty-six male rats were allocated into seven equal groups. Hyperalgesia was caused by intraperitoneal single dose administration of cisplatin (1mg/kg) and assessed by utilizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The major antioxidant enzymes that can eliminate H 2 O 2 are catalase, glutathione peroxidase and peroxiredoxins ( Phaniendra et al, 2015 ). It was previously demonstrated that M. rotundifolia extract significantly improved the activities of these enzymes in the liver homogenate after carrageenan injection ( Mohajjel Nayebi et al, 2021 ). Hepatic biomarkers (ALT, AST, and Bilirubin) were assayed as well in this work.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The major antioxidant enzymes that can eliminate H 2 O 2 are catalase, glutathione peroxidase and peroxiredoxins ( Phaniendra et al, 2015 ). It was previously demonstrated that M. rotundifolia extract significantly improved the activities of these enzymes in the liver homogenate after carrageenan injection ( Mohajjel Nayebi et al, 2021 ). Hepatic biomarkers (ALT, AST, and Bilirubin) were assayed as well in this work.…”
Section: Discussionmentioning
confidence: 94%
“…H 2 O 2 exposure significantly decreased the latency of the tail reflex. Several studies have related hyperalgesia to oxidative stress and showed that it can be attenuated by antioxidant treatments ( Mohajjel Nayebi et al, 2021 ). The extract treated groups, whether in “Tap water” or “H 2 O 2 ” conditions showed dose-dependent responses.…”
Section: Discussionmentioning
confidence: 99%